Variation in female aggression in 2 three-spined stickleback populations with female throat and spine coloration. Issue 3 (7th March 2018) - Yong, Lengxob; Lee, Brittney; McKinnon, Jeffrey S; ,
Abstract: Despite growing interest in female ornament evolution, we still have a rudimentary understanding of female display traits relative to similar traits in males. Under one popular adaptive scenario, female ornaments are hypothesized to function in female–female competition and serve as badges of status, such that their expression is linked with elevated aggression in some cases. In this study, we investigated the relationship between 2 female ornaments—male-like red throat color and red spine coloration—and female aggression in 2 independently derived stream-resident populations of three-spined stickleback Gasterosteus aculeatus . Using simulated intrusions, we tested whether females with redder ornaments were generally more aggressive, and for variation in aggressive and social behaviors between the 2 populations. We found that the red intensity of the throat and spine did not predict aggression levels in either population, suggesting a limited role for both female ornaments during female–female interaction. The 2 populations exhibited different levels of aggressive behaviors, unrelated to the color patches. Our results suggest that variation in selective pressures between populations may promote interpopulation variance in aggressive behavior but not the correlation between female ornamentation and aggression, and raise the possibility that red coloration may have evolved through different mechanisms or processes in the 2 populations.